Fatigue cracking of bituminous paving mixtures - Read, John (1996)
This dissertation is concerned with the fatigue cracking of bituminous paving mixtures. It considers both the life to crack initiation and the life for crack propagation, including the development of a method for calculating the number of wheel load applications to either critical or failure condition.